Ternstroemia sierragordensis (Pentaphylacaceae), a new cloud forest tree species from Querétaro and San Luis Potosí, Mexico - Alcántara-Ayala, Othón; Luna-Vega, Isolda; Alvarado-Sizzo, Hernán (Phytotaxa, 2025)
Ternstroemia sierragordensis, a new species from the states of Querétaro and San Luis Potosí, Mexico, is described and illustrated, using molecular, phylogenetic, and morphological data. This tree inhabits a conserved tropical montane cloud forest with Liquidambar styraciflua, Pinus greggii, Tilia mexicana, Podocarpus matudae, and Magnolia aff. schiedeana and Quercus spp., as part of the canopy. This new species is related to Ternstroemia huasteca, but differs because it is a taller tree, the evident presence of lenticels in the bark and branches, the crenate margin of the leaves, and the long and thin peduncles.